Review of athletic guidelines for high-altitude training and acclimatization - Ramchandani, R.; Florica, I. T.; Zhou, Z.; Alemi, A.; Baranchuk, A. (High Altitude Medicine & Biology, 2024)
Introduction: Exposure to high altitude results in hypobaric hypoxia with physiological acclimatization changes that are thought to influence athletic performance. This review summarizes existing literature regarding implications of high-altitude training and altitude-related guidelines from major governing bodies of sports.